Empowering Women Farmers in Facing Climate Change Through the Horticulture Agriculture Program on Peatland - Manullang, Leonardo; Rahmad Hidayat; Dhoiri Mulyadi (ENVIBILITY: Journal of Environmental and Sustainability Studies, 2024)
Women farmers are a group that is vulnerable to the impacts of climate change. In their activities they are very dependent on natural resources and climate. Unfortunately, women farmers are often left out of planning and policies in efforts to overcome this problem. PT Kilang Pertamina Internasional Refinery Unit II Production Sungai Pakning this is a problem that can result in women farmer groups becoming increasingly marginalized. For this reason, the company, through its CSR program, carries out empowerment to increase the capacity of women farmers through the development of horticultural agriculture on peatlands in facing climate change problems. This research aims to see how the CSR implementation of PT Kilang Pertamina Internasional Refinery Unit II Production Sungai Pakning through the horticultural agriculture program empowers women farmers in facing the impacts of climate change. This research uses descriptive qualitative methods to explain the authentic experiences of women farmers in the empowerment process which plays a role in responding to the impacts of climate change. The research informants were female farmers who were members of the peatland horticultural farming program. Data collection methods are carried out through interviews, documentation, observation. The results of the research show that empowering women farmers through a horticultural farming program on peatlands is able to increase the capacity of women farmers, especially their ability to deal with climate change and are able and encourage initiatives to make alternative choices in an effort to face the impacts of climate change. Women farmers are no longer passive members who simply take part in activities, women farmers through their capacities become subjects who have political power to accommodate their interests.